1995
DOI: 10.1097/00003246-199510000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life measures before and one year after admission to an intensive care unit

Abstract: Patients admitted to intensive care tend to have a decrease in the level of activity and activities of daily living 1 yr after their ICU stay, although in the very elderly, perceived health status increases. As well, the majority (89%) of patients return home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
2
7

Year Published

1997
1997
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 14 publications
3
56
2
7
Order By: Relevance
“…This is consistent with other studies [5,6] where hospital mortality rates have been found to be twice the ICU mortality. When making the decision whether to admit a patient to ICU, it is important to consider hospital mortality as well as ICU outcomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with other studies [5,6] where hospital mortality rates have been found to be twice the ICU mortality. When making the decision whether to admit a patient to ICU, it is important to consider hospital mortality as well as ICU outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Significant variations have been found in ICU use by hospital characteristics and geographical location that remained significant after controlling for severity of illness and patient demographic characteristics [4]. In addition, studies show that hospital mortality rates were as high as twice ICU mortality rates [5,6]. It is clear that a contemporary survey of current practice as regards ICU admission and outcome in HIV-positive patients was warranted.…”
mentioning
confidence: 99%
“…Even though mortality as an outcome measure has often been challenged [9], this measure remains one of the key parameters. The reasons are the simplicity of its definition and the ease of obtaining results (at least with respect to ICU or hospital mortality).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Further, it seems useful in predicting outcomes other than death, such as healthrelated quality of life and health services utilization. [19][20][21][22][23] Data about functional status and well-being are theoretically easy to obtain; one need only ask or observe. Most assessments can be made quickly and with a minimum of bother to patients.…”
mentioning
confidence: 99%